Soil water potential on lettuce production - Cardoso, Gabriel Greco de Guimarães [UNESP]; Klar, Antônio Evaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2009)
The scope of this experiment is to study the influence of soil water potential on lettuce productivity, particularly in relation to deficit and excess of water. Four lettuce cultivars (Americana, Roxa, Crespa and Mimosa), four minimum soil water potential (-0,001, -0,005, -0,012 and 0,022 MPa) and three replicates in experimental randomized design. The results allowed concluding that the -0,012 MPa has the tendency to produce the highest green mass among her soil water potential applied. The Mimosa showed the tendency to produce the highest evapotranspiration among the cultivars. The cultivars Americana e -0,05 MPa was the best combination (148,33g) the worst was the Roxa and -0,022 MPa minimum soil water potential.
Potenciais de água no solo na produção de alface
Keywords: Blade of irrigation; Evapotranspiration; Water deficit